Reactive polymers fundamentals and applications : a concise guide to industrial polymers - Fink, Johannes Karl (PDL handbook series., 2005)
Loaded with practical knowledge, Reactive Polymers Fundamentals and Applications: A Concise Guide to Industrial Polymers comprehensively presents the state-of-art of methods and materials for the formulation of polymeric resins. It is an indispensable tool for chemists, engineers, and manufacturers who use, formulate, and cure raw materials into final products. The text focuses on the chemical modification of properties during the final stage of part fabrication from plastics. Newer applications range from the small scale, such as dental fillings, to industrial processes for batch fabrication. The book covers resin groups in major use in industry and under active research and development.